Domestic Factors on China’s Green Belt and Road Initiatives: Comparing Indonesia and Thailand - Shafira, Rizka Bunga; Yeremia, Ardhitya Eduard (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2025)
China’s implementation of the Green Belt and Road Initiative (BRI) reflects a shift in its foreign policy to support global energy transition and sustainable development. However, there is a notable gap between the initiative’s objectives and its outcomes in host countries. While the Green BRI aims to showcase China’s commitment to green investments, its energy investments in Indonesia remain heavily focused on fossil fuels, particularly coal. In contrast, China’s renewable energy investments are prominent in Thailand. This study examines the implementation of the Green BRI in Indonesia and Thailand, analyzing how the energy mixes and investment portfolios. This study involving literature review and analysis of secondary data sources analyzed through the lens of Global China. This study argues that the divergence in Green BRI implementation across Southeast Asia reflects not merely China’s flexibility, but the differentiated capacities of host countries to absorb, steer, or resist foreign investment agendas. Ultimately, Green BRI is highly adaptive, and its outcomes are co-produced through complex interactions between China’s intentions and the domestic landscapes of partner countries. This study contributes by highlighting the critical role of domestic political and economic contexts in shaping China’s green investments.